Acute Impact of Tobacco vs Electronic Cigarette Smoking on Oxidative Stress and Vascular Function - Carnevale, Roberto; Sciarretta, Sebastiano; Violi, Francesco; Nocella, Cristina; Loffredo, Lorenzo; Perri, Ludovica; Peruzzi, Mariangela; Marullo, Antonino G M; De Falco, Elena; Chimenti, Isotta; Valenti, Valentina; Biondi-Zoccai, Giuseppe; et al. (Chest, 2016)
The vascular safety of electronic cigarettes (e-Cigarettes) must still be clarified. We compared the impact of e-Cigarettes vs traditional tobacco cigarettes on oxidative stress and endothelial function in healthy smokers and nonsmoker adults. A crossover, single-blind study was performed in 40 healthy subjects (20 smokers and 20 nonsmokers, matched for age and sex). First, all subjects smoked traditional tobacco cigarettes. One week later, the same subjects smoked an e-Cigarette with the same nominal nicotine content. Blood samples were drawn just before and after smoking, and markers of oxidative stress, nitric oxide bioavailability, and vitamin E levels were measured. Flow-mediated dilation (FMD) was also measured. Smoking both e-Cigarettes and traditional cigarettes led to a significant increase in the levels of soluble NOX2-derived peptide and 8-iso-prostaglandin F2α and a significant decrease in nitric oxide bioavailability, vitamin E levels, and FMD. Generalized estimating equation analysis confirmed that all markers of oxidative stress and FMD were significantly affected by smoking and showed that the biologic effects of e-Cigarettes vstraditional cigarettes on vitamin E levels (P = .413) and FMD (P = .311) were not statistically different. However, e-Cigarettes seemed to have a lesser impact than traditional cigarettes on levels of soluble NOX2-derived peptide (P = .001), 8-iso-prostaglandin F2α (P = .046), and nitric oxide bioavailability (P = .001). Our study showed that both cigarettes have unfavorable effects on markers of oxidative stress and FMD after single use, although e-Cigarettes seemed to have a lesser impact. Future studies are warranted to clarify the chronic vascular effects of e-Cigarette smoking.